Global Strategic Maritime Infrastructure and its Impact on Shipping Industry and Supply Chains Management - Andrzej S. GRZELAKOWSKI (Communications of International Proceedings, 2022)
The main subject of research involves the characteristics and assessment of the quality of technical and operational parameters and the functionality level of the largest oceanic canals which constitute key objects of maritime infrastructure and links in the global supply chains. These are objects of strategic importance for the development of trade and maritime transport, determining the efficiency and effectiveness of commodity flow on a global scale. They also co-develop the supply chain resistance to upheaval and disturbances they are subject to in a turbulent environment. They also determine their visibility and flexibility. This research aimed to assess the current development of these facilities and their importance for maritime navigation, and to determine their impact on the efficiency of global supply chains. In research, the following methods were applied: statistical analysis, case study, factor analysis (FA) and desk research, using available reports, accounts and expert opinions. The obtained research results indicate that: 1/ maritime canals are of key importance for the construction of economic, ecological and spatial order within the global transport and logistics space, 2/ they create a new quality in the management of this space, which allows to optimize the logistics processes and provides possibilities for rationalizing the global trade transport service model in terms of time and costs, 3/ under full operational efficiency, they generate significant added value for  maritime carriers.
Keywords: strategic maritime infrastructure; maritime canals and their development; global supply chains management and trade distribution; world shipping industry